Operational permits and brandings of savings and loan cooperatives and sharia financing (KSPPS) in legal validity perspective - Anjar Kususiyanah; Soleh Hasan Wahid; Wahyu Saputra (State Institute of Islamic Studies (IAIN) Salatiga, 2021)
This article described the legal validity of Savings and Loan Cooperatives and Sharia Financing (KSPPS) in East Java Region, especially regarding operational permits and their brandings. Most of them have KSPPS operational permits but in their operations use Baitul Mall Wa Tamwil (BMT) brand. Meanwhile, based on Chapter 2 Article 2 Point 7 of the Regulation the Minister of Cooperatives and Small and Medium Enterprises (SMEs) Number: 11/PER/M.KUKM/XII/2017, it is mandatory for every cooperative branch office and service network to display the cooperative identity either the name or logo, and not the BMT brand. The problem in this study was discussed using legal validity theory from philosophical, juridical and sociologicaldimensions. This was a qualitative research with a sociological, juridical, philosophical approach. Data collection techniques were divided into two, namely literature study to explore legal documents as data to review philosophical and juridical aspects and field studies to explore information from KSSPS in East Java to analyze the sociological aspects of the validity of the Regulation. The findings of the research were: the legal validity of the Ministerial Regulation Number: 11/PER/M.KUKM/XII/2017 from a philosophical point of view is not in line with the legal ideals of cooperatives in Indonesia. While from a juridical side, there is a legal vacuum. In addition, from a sociological dimension, it has not run perfectly due to non-optimal socialization from policy makers.